Where to look: sources of research in paramedicine. (2nd August 2021) - Holland, Matt; Dutton, Michelle; Glover, Steve
Abstract : This article explains how to approach searching for paramedicine research, and the order in which you should consider types of sources, from synthesised sources to individual studies. Databases and sources for literature are covered and common issues about the search process are addressed, including when a search is complete and finding a gap in the literature.